Expression and function of exportin 6 in full-grown and growing porcine oocytes - Asuka ONUMA; Yoshie A. FUJIOKA; Wataru FUJII; Koji SUGIURA; Kunihiko NAITO (The Society for Reproduction and Development, 2019)
Exportin 6, which functions specifically in the nuclear export of actin family proteins, has been reported to be absent in immature Xenopus oocytes, which have a huge nucleus containing a large amount of actin. In mammalian oocytes, however, the presence and the function of exportin 6 remain uninvestigated. In this study, we assessed the expression and effects of exportin 6 on meiotic resumption in porcine oocytes after cloning porcine exportin 6 cDNA and carrying out overexpression and expression inhibition by mRNA and antisense RNA injection, respectively. We found for the first time that exportin 6 was expressed in mammalian full-grown germinal-vesicle-stage oocytes and was involved in the nuclear export of actin. In contrast, exportin 6 was absent from the growing oocytes, which are meiotically incompetent and maintain the germinal-vesicle structure in the long term; the regulatory mechanism appeared to be active degradation. We examined the effects of exportin 6 on meiotic resumption of porcine oocytes and noted that its expression did not affect the onset time but increased the rate of germinal vesicle breakdown at 24 h via regulation of the nuclear actin level, which directly influences the physical strength of the germinal-vesicle membrane. Our results suggest that exportin 6 affects the nuclear transport of actin and meiotic resumption in mammalian oocytes.